Dual-wavelength erbium-ytterbium co-doped fibre laser operating at 1064 and 1534 nm - Jusoh, Z.; Harun, Sulaiman Wadi; Shahabuddin, N.S.; Ahmad, Harith; Paul, Mukul Chandra; Das, S.; Dhar, A.; Pal, M. (Institute of Physical Optics, 2014)
We demonstrate a simple erbium-ytterbium co-doped fibre laser with dual-wavelength output, which operates at 1064 and 1534 nm using a single gain medium. The laser operates on a recently developed erbium-ytterbium doped fibre (EYDF) with the erbium and ytterbium ion concentrations of 1000 and 1500 ppm respectively, in conjunction with a linear cavity setup based on two fibre Bragg gratings. By pumping a 5 m long EYDF with a 980 nm laser diode, simultaneous generation at 1064 and 1534 nm is reached, with the corresponding peak powers of 3.4 and –8.3 dBm. The lasing thresholds are 40 and 80 mW respectively for 1064 and 1534 nm.